2015
DOI: 10.1111/bju.13205
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of mass media public health campaigns. Be Clear on Cancer ‘blood in pee’: a case in point

Abstract: all referrals of patients deemed to be at risk of urological cancer by the referring primary healthcare physician to Imperial College NHS Healthcare Trust were screened. Data were collected on age and sex and whether the referral was for visible haematuria, non-visible haematuria or other suspected urological cancer. In addition to referral data, hospital episode data for all new renal cell (RCC) and upper and lower tract transitional cell carcinoma (TCC), as well as testicular and prostate cancer diagnoses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 11 publications
4
27
0
Order By: Relevance
“…However, while pilot data showed a 48% increase in BC diagnoses when this campaign was trialled , these results have not been replicated following national rollout of the campaign. At one centre the number of diagnoses actually decreased despite a 92% increase in haematuria referrals .…”
Section: Discussionmentioning
confidence: 98%
“…However, while pilot data showed a 48% increase in BC diagnoses when this campaign was trialled , these results have not been replicated following national rollout of the campaign. At one centre the number of diagnoses actually decreased despite a 92% increase in haematuria referrals .…”
Section: Discussionmentioning
confidence: 98%
“…HughesHallett et al (22) have shown that the effectiveness of public health campaigns was temporary on the society and generally increased hospital admission rates, but not cancer diagnosis rates. If so, it would be wise to concentrate more on educating people to raise awareness, rather than making high-budget campaigns to reduce health spending.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent urologic mass media campaign 'blood in pee' has not led to a significant change in the diagnosis of targeted cancers across a large catchment [21] . In the urological field, awareness campaigns are mainly focused on malignant diseases [22] .…”
Section: Discussionmentioning
confidence: 99%